Integration atoms in octa- and tetrahedrical internodes of BCC crystals with a free surface - Zolotarenko, Ol.D.; Rudakova, O.P.; Zolotarenko, An.D.; Shchur, D.V.; Gavrilyuk, N.A.; Kartel, N.T.; Zolotarenko, O.D.; Mashira, V.A. (Recent Contributions to Physics, 2022)
The physical properties of crystals are determined by their chemical nature, the structure of both the entire volume and the surface layer. The surface of a metal, ionic or covalent crystal and semiconductor can be considered as a special state of matter with its own chemistry and physics. The interest in the problem of solid state surfaces, in the science of surface, in the physics of thin films is stimulated by advances in solid state physics, technical innovations, opportunities to create new film materials with unique properties, the challenges of modern technology, the requirements of technology to create devices for computing technology and microelectronics. In this work the processes of redistribution of infiltration atoms along the surface and bulk inter-nodes are considered, the equilibrium distribution of infiltrated atoms on the surface and in the crystal volume, as well as the effect of external pressure on the surface and bulk distribution of infiltration atoms, are studied. Knowledge of the processes of redistribution of infiltration atoms along the inter-nodules of a crystal and of the reasons causing them may allow the purposeful formation of these processes for the purpose of obtaining certain physical characteristics of materials. The kinetics of inter-nodal rearrangement of infiltration atoms has been studied for metals and ordering alloys of various structures.